Comparison of Neotectonic Intermontane Basins of Northern Armenia and Eastern Turkey - Trifonov, V. G.; Tesakov, A. S.; Simakova, A. N.; Celik, H.; Frolov, P. D.; Bachmanov, D. M.; Trikhunkov, Ya. I. (Pleiades Publishing Inc, 2024)
The results of a comparative analysis of the structure and history of the Neogene-Quaternary development of 18 intermontane basins in Northern Armenia and Eastern Turkey are presented. The research is based on expeditionary works carried out by the authors in 2012-2023 and supplemented by published materials from other researchers. Paleontological, magnetostratigraphic, and radioisotope data on the stratigraphy of the basins are analyzed. The comparison made it possible to identify four stages of basin development, expressed by the type of sedimentation: (i) marine sedimentation; (ii) predominantly lacustrine accumulation of fine-grained clastic material transported from low uplifts; (iii) lacustrine-alluvial sedimentation with a significant proportion of coarse material carried down from neighboring uplifts: (iv) involvement of the basins in the total uplift of the region, which in most basins is expressed by increased incision of watercourses into previously emerged landforms and in the Sevan depression is combined with ongoing lacustrine-alluvial sedimentation. Consistent rejuvenation of stages (i)-(iii) of basin development in the northern direction is revealed, caused by the growth and northward expansion of uplift of the Taurus Ridge in the process of its thrusting onto the Arabian Plate. At the same time, development of the basins revealed the impact of tectonic events in the Middle and South Caspian. It was expressed in the Early Pliocene by an unconformity and the appearance of coarse-clastic rocks, reflecting the increasing contrast of vertical movements between the Caucasian and Caspian regions, and at the end of the Late Pliocene by penetration of waters of the Akchagylian transgression of the Caspian Sea into some basins. These features of the development of the basins did not depend on differences in their origin, which was governed by the influence of several factors. Among them, the main ones were movements on faults as a result of the interaction of lithospheric blocks, and subsidence, caused by movements of sublithospheric masses, expressed by volcanism. Secondary roles were played by the behavior of the ophiolitic substrate and the tectonovolcanic damming of river valleys.
Keywords: tectonic development; active fault zones; volcanic fields; intermontane basin origin; Neogene-Quaternary stratigraphy